Current ART, determinants for virologic failure and implications for HIV drug resistance: an umbrella review - SeyedAhmad SeyedAlinaghi; Amir Masoud Afsahi; Ali Moradi; Zohal Parmoon; Pedram Habibi; Pegah Mirzapour; Mohsen Dashti; Afsaneh Ghasemzadeh; Elaheh Karimi; Foziye Sanaati; Zahra Sadat Hamedi; Ayoob Molla; et al. (2023)
Abstract Objective The purpose of this study is to investigate the incidence of determinants for virologic failure and to identify predisposing factors to enhance treatment efficacy. Tackling this global public health issue is the key to reducing the rate of virological failure and increasing the success of treatment for those living with HIV. Methods This umbrella review delves into various aspects of current anti-retroviral therapy (ART) which is the primary treatment for human immunodeficiency virus (HIV) infection. Comprehensive searches were conducted in online databases including PubMed, Embase, Scopus, and Web of Science, up to May 26, 2023. Following the screening and selection of relevant articles, eligible articles were included in the data extraction. This study adhered to the PRISMA guideline to report the results and employed the NIH quality and bias risk assessment tool to ensure the quality of included studies. Results In total, 40 review studies published from 2015 to 2023 were included. The bulk of these studies concurred on several major factors contributing to HIV drug resistance and virological failure. Key among these were medication adherence, baseline and therapeutic CD4 levels, the presence of co-infections, and the advanced clinical stage of the infection. Conclusion The resistance to HIV drugs and instances of determinants for virologic failure have a profound impact on the life quality of those infected with HIV. Primary contributors to this scenario include insufficient adherence to treatment, decreased CD4 T-cell count, elevated viral levels, and certain treatment regimens. Implementing appropriate interventions could address these issues. Sub-Saharan Africa exhibits elevated rates of determinants for virologic failure, attributed to the delay in HIV testing and diagnosis, and late initiation of antiretroviral therapy (ART). It is essential to undertake further research aimed at enhancing the detection of resistance in HIV patients and mitigating viral failure by addressing these underlying causes.